Construction of nearly uniform designs on irregular regions. Issue 17 (2nd September 2017) - Qi, Zong-Feng; Yang, Jian-Feng; Liu, Yan; Liu, Min-Qian
ABSTRACT: The uniform design is a kind of important experimental design which has great practical value in production and living. Most existing literatures on this topic focus on the construction of uniform designs on regular regions. However, because of the complexity of practical situations, the irregular design region is more common in real life. In this paper, an algorithm is proposed to the construction of nearly uniform designs on irregular regions. The basic idea is to make use of uniform designs on a larger regular region with the irregular region being a subregion. Some theoretical justifications on the proposed algorithm are provided. Both the comparisons with the existing results and a real-life example show that our proposed algorithm is effective.